Formaldehyde Gas Sensing Characteristics of ZnO-TiO2 Gas Sensors - Jaebum Park; Jihoon Lee; Myung Sik Choi; Jeung-Soo Huh (Chemosensors, 2023)
Since the increase in the emission of various Volatiles Organic Compounds, gas and formaldehyde gas have had a harmful effect on the human body, and gas sensors that can measure those gases were fabricated in this study. After Pt coating was performed on the alumina substrate, Zn seed layers were fabricated. Nanostructures were formed through sonochemical synthesis by varying the ratio of ZnO and TiO2. Thereafter, the reactivity and recovery properties were compared and evaluated according to the concentrations of formaldehyde and toluene gas. The ZnO(99%)-TiO2(1%) gas sensor showed meaningful selectivity of about 40% or more at a concentration ranging from 5 to 20 ppm (high concentration) of formaldehyde and toluene gas, and showed a low selectivity of about 5% or more for a concentration ranging from 0.1 to 1 ppm (low concentration) of formaldehyde and toluene gas. This sensor can be optimized to have a meaningful selectivity of formaldehyde gas compared to other Volatiles Organic Compounds gases by optimizing the ZnO-TiO2 nanostructure.